2020
DOI: 10.1016/j.dnarep.2020.102924
|View full text |Cite
|
Sign up to set email alerts
|

How to fix DNA-protein crosslinks

Abstract: Proteins that act on DNA, or are in close proximity to it, can become inadvertently crosslinked to DNA and form highly toxic lesions, known as DNA-protein crosslinks (DPCs). DPCs are generated by different chemotherapeutics, environmental or endogenous sources of crosslinking agents, or by lesions on DNA that stall the catalytic cycle of certain DNA processing enzymes. These bulky adducts impair processes on DNA such as DNA replication or transcription, and therefore pose a serious threat to genome integrity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 153 publications
(224 reference statements)
0
29
0
Order By: Relevance
“… Stingele et al (2017) have proposed that each constituent of DPC: DNA, protein, and the covalent linkage between them might be processed by three different repair mechanisms. A recent paper by Kühbacher and Duxin (2020) provides comprehensive review on the formation and repair of DPCs. In this review, we summarize the current knowledge regarding the repair mechanisms involved in removal of DHCs induced by various genotoxic agents.…”
Section: Introductionmentioning
confidence: 99%
“… Stingele et al (2017) have proposed that each constituent of DPC: DNA, protein, and the covalent linkage between them might be processed by three different repair mechanisms. A recent paper by Kühbacher and Duxin (2020) provides comprehensive review on the formation and repair of DPCs. In this review, we summarize the current knowledge regarding the repair mechanisms involved in removal of DHCs induced by various genotoxic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Repair mechanisms can target different components of a DNA–protein cross-link ( i.e. , the DNA molecule, the cross-link bond, or protein) and may depend on the stage of the cell cycle ( 27 , 28 , 36 ). Most DNA–protein cross-links are too large for DNA polymerase bypass ( 37 ), and proteases are believed to cleave the proteins to smaller peptides that can be repaired by nucleotide excision repair (NER) ( 38 ) or homologous recombination (HR) or bypassed by translesion synthesis (TLS) polymerases ( 39 ).…”
mentioning
confidence: 99%
“…Reverses SPRTN monoubiquitylation to promote its chromatin access [65] Trends in Cell Biology OPEN ACCESS domain (SPRTN) and the proteasome, offers an important means of recognizing and resolving this bulky and highly heterogenous class of DNA lesion [12]. While the CMG is ultimately able to bypass DPCs on the leading strand in a manner that requires the helicase regulator of telomere length 1 (RTEL1) [60], it temporally stalls at these lesions, triggering DPC ubiquitylation by the replisome-associated ubiquitin ligase TRAF-interacting protein (TRAIP), which appears to promiscuously ubiquitylate proteins ahead of the CMG [61].…”
Section: Vcpip1mentioning
confidence: 99%
“…Specifically, it was recently shown that the fork-associated protein HMCES forms DPCs at abasic sites to prevent their error-prone processing, with HMCES protein adducts being subsequently resolved via ubiquitin-dependent proteolysis [67]. Outside the context of DNA replication, when DPCs cannot be resolved via the replisome, SUMOylation is indispensable for DPC removal in a manner that may involve downstream processing of the adducted protein via ubiquitylation and the proteasome [12,68,69].…”
Section: Vcpip1mentioning
confidence: 99%
See 1 more Smart Citation